Vibration control of a membrane antenna structure using cable actuators. Issue 5 (March 2018) - Liu, Xiang; Zhang, Hua; Lv, Liangliang; Peng, Fujun; Cai, Guoping
Highlights: A control strategy of using cable actuators to control the vibration of a membrane antenna structure is proposed. A feedback controller is designed based on the Lyapunov's stability theory. The optimal placement of the cable actuators is studied. Abstract: This paper presents a control strategy of using cable actuators to control the vibration of a membrane antenna structure. The tension cables of the membrane antenna structure are used as actuators, the vibration of the structure can be suppressed by controlling the tension force in the cable actuators. First, the antenna structure with cable actuators is discretized by the finite element method (FEM), and governing equation of the whole structure is established. Then, a controller is designed based on the Lyapunov's stability theory, and the mechanism of this controller is studied through a simple single-degree-of-freedom (SDOF) system. The optimal placement of the cable actuators is also studied numerically in this paper. Simulation results indicate that vibration of the membrane antenna structure can be suppressed effectively by the cable actuators, and optimally placed cable actuators can produce better control effect with smaller control input.